Neonatal Cholestasis: A Rare and Unusual Presentation of Pituitary Stalk Interruption Syndrome - R. El Qadiry; A. Ouayad; H. Nassih; A. Bourrahouat; I. Ait Sab (Case Reports in Endocrinology)
Pituitary stalk interruption syndrome (PSIS) is a very rare entity, and the clinical manifestations are nonspecific. Neonatal cholestasis due to endocrine disorders is rare and poorly recognized. Our case report describes a case of PSIS in a Moroccan infant revealed by isolated neonatal cholestasis, which is an unusual presentation in children. Case report. A 40-day-old girl was admitted to our department for progressive cholestatic jaundice appeared on the third day of life. She was born from a non-consanguineous marriage, and her prenatal and perinatal history went without incident. Physical examination showed icteric skin and sclera, without hepatomegaly. Analysis of pituitary hormones revealed panhypopituitarism. On brain magnetic resonance imaging (MRI), the pituitary stalk was absent, the posterior pituitary was ectopic, and the anterior pituitary was hypoplastic. The patient was diagnosed with interrupted pituitary stalk syndrome. The treatment consisted of hormone replacement with rapid improvement of her clinical condition. Conclusion. Panhypopituitarism, a consequence of PSIS, is a rare cause of neonatal cholestasis. However, pediatricians should keep this syndrome in mind for patients who present with neonatal cholestasis.